(untitled) (مجلة العلوم الشاملة, 2026)
Recently the closed form estimators of the two parameter beta distribution have been proposed and investigated by several authors. This is due to its importance over the maximum likelihood estimates sometimes. In this paper we present new closed form to estimate beta parameters with simple formula. The proposed methods are compared with the maximum likelihood and moments estimates through simulation study. The results showed that the proposed method efficiently estimated the parameters and its performance get closer to the maximum likelihood and the moment estimates as the sample size increases.